On the Basic Concepts of UWB Radar Scan - Astanin, L.Yu.; Kostylev, A.A.; Fliorova, A.A. (Радиофизика и радиоастрономия, 2002)
In this paper, the terms in wide use, the Ultra Wideband (UWB) signal and the Ultra Shot Impulse (USI), are discussed. Their usage conditions are considered and the difference in meanings is determined. As main tool for describing the power requirements to UWB Radar, the generalized Radar Range Equation (RRE) valid to arbitrary width of the spectrum is employed. The assumptions as to the UWB Radar characteristics allowing to represent the RRE in similarity to the traditional form are considered. The use of the Impulse Active Antenna Array can be a way to the UWB power problem solution. The problems regarding the high peak power UWB signals are posed. It is possible, as demonstrated, to produce the complex UWB pulse signal with large timebandwidth product.